2006
DOI: 10.1063/1.2214156
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the n-type conductivity of InN: The role of positively charged dislocations

Abstract: As-grown InN is known to exhibit high unintentional n-type conductivity. Hall measurements from a range of high-quality single-crystalline epitaxially grown InN films reveal a dramatic reduction in the electron density (from low 1019 to low 1017cm−3) with increasing film thickness (from 50to12000nm). The combination of background donors from impurities and the extreme electron accumulation at InN surfaces is shown to be insufficient to reproduce the measured film thickness dependence of the free-electron densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
104
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 19 publications
(16 reference statements)
5
104
2
3
Order By: Relevance
“…2 Intrinsic point defects have been accounted for multiple important mechanisms in the material. [3][4][5][6][7] Among them, isolated and complexed In vacancies (V In ) and N vacancies (V N ) are expected to be the dominant intrinsic acceptors and donors, respectively, according to latest density functional theory calculations. [8][9][10][11][12] Nevertheless, unambiguous experimental evidence on their nature and characteristics is still relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…2 Intrinsic point defects have been accounted for multiple important mechanisms in the material. [3][4][5][6][7] Among them, isolated and complexed In vacancies (V In ) and N vacancies (V N ) are expected to be the dominant intrinsic acceptors and donors, respectively, according to latest density functional theory calculations. [8][9][10][11][12] Nevertheless, unambiguous experimental evidence on their nature and characteristics is still relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However H c2 values are 0.3410 and 1.2 T for the B ʈ c-axis, and B Ќ c-axis, respectively. These values are much greater than the critical magnetic field of In which is 0.023 T. 11 This observation alone may suggest that it is bulk InN rather than In dots/chains that become superconductive. If it is InN becoming superconducting two equally plausible mechanisms may explain the observed behavior.…”
mentioning
confidence: 99%
“…Indium-rich GaInN can be utilized in optoelectronic device applications extending the well-known ultraviolet and blue spectral region applications of the Ga rich material to the near infrared, thus covering wavelengths from 200 to 1650 nm using a single material system. [6][7][8][9][10][11] There is little experimental data on the electrical properties of InN particularly at low temperatures. Recently, Inushima et al 12 has reported the observation of superconducting behavior of InN.…”
mentioning
confidence: 99%
“…However, it is still difficult to reduce the dislocation density to below 10 9 cm -2 . Threading dislocations have been suggested to be a source of unintentional n-type doping in InN, [8][9][10] as well as scattering centers that decrease the electron mobility 9 and nonradiative recombination centers. 11 Therefore, threading dislocations should be reduced.…”
Section: Mev At 4 K Copyright 2011 Author(s) This Article Is Distrimentioning
confidence: 99%